Measurement of the CP properties of Higgs boson interactions with $$τ $$ τ -leptons with the ATLAS detector - G. Aad; B. Abbott; D. C. Abbott; K. Abeling; S. H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A. C. Abusleme Hoffman; B. S. Acharya; B. Achkar; et al. (European Physical Journal C: Particles and Fields, 2023)
Abstract A study of the charge conjugation and parity ( $$CP$$ CP ) properties of the interaction between the Higgs boson and $$τ $$ τ -leptons is presented. The study is based on a measurement of $$CP$$ CP -sensitive angular observables defined by the visible decay products of $$τ $$ τ -leptons produced in Higgs boson decays. The analysis uses 139 fb $$^{-1}$$ - 1 of proton–proton collision data recorded at a centre-of-mass energy of $$\sqrt{s}= 13$$ s = 13 TeV with the ATLAS detector at the Large Hadron Collider. Contributions from $$CP$$ CP -violating interactions between the Higgs boson and $$τ $$ τ -leptons are described by a single mixing angle parameter $$φ _{τ }$$ ϕ τ in the generalised Yukawa interaction. Without constraining the $$H→ τ τ $$ H → τ τ signal strength to its expected value under the Standard Model hypothesis, the mixing angle $$φ _{τ }$$ ϕ τ is measured to be $$9^{° } ± 16^{° }$$ 9 ∘ ± 16 ∘ , with an expected value of $$0^{° } ± 28^{° }$$ 0 ∘ ± 28 ∘ at the 68% confidence level. The pure $$CP$$ CP -odd hypothesis is disfavoured at a level of 3.4 standard deviations. The results are compatible with the predictions for the Higgs boson in the Standard Model.